Management of Work and/or Human Resources? Contemporary Dilemmas of the Judiciary and the Public Sector - Rymaniak , Janusz; Surmacz , Beata (Studia Oeconomica Posnaniensia, 2016)
The authors look for relationships between work design and the application of human resource management practices. They compare the general, as well as judiciary, tendencies on the basis of questionnaire research. They verify the relation of the developmental trends of work design opinions, as well as the acceptance of different practices of the HRM. Additionally, they show the directions of further research.